Non-typhoidal Salmonella among slaughterhouse workers and in the pork value chain in selected districts of Uganda - Kivali, Velma; Roesel, Kristina; Dohoo, I.; Alinaitwe, Lordrick; Bugeza, James K.; Hoona, J.J.; Mugizi, Denis R.; Kankya, C.; Sinh Dang-Xuan; Szabo, I.; Rösler, U.; Friese, A.; et al. (Frontiers Media, 2024)
Introduction: Non-typhoidal Salmonella (NTS) is a major cause of gastroenteritis worldwide, often associated with meat consumption and meat processing. Research on NTS infection and circulating serovars in meat value chains in Uganda is limited. We aimed to establish NTS prevalence, antimicrobial resistance, and risk factors among slaughterhouse workers, and to identify potentially zoonotic serovars in the pork value chain.